Canada. Annual report 2008 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
The activities of the Inter-American Institute for Cooperation on Agriculture are presented, by the Delegation of Canada, during 2008, focused on the development of agriculture and rural life, making available its installed technical capacity within the scope of its strategic action priorities; in contribution to the repositioning of agriculture and rural life, promotion of trade and competitiveness of agribusiness, strengthening of agricultural health and food safety systems, promotion of sustainable management of natural resources and the environment, strengthening of rural communities using the territorial approach, and finally the introduction of technology and innovation for the modernization of agriculture and rural life.